2017
DOI: 10.1007/s00432-017-2533-0
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative evaluation of mobile cancer apps with particular attention to the target group, content, and advertising

Abstract: Almost half of the tested apps were deficient or insufficient. In order to improve safety of patients using apps, some regulation seems mandatory. Putting apps under the legislation for medical products might be one way to better regulate and control quality. Second, efforts should focus on the development of checklists that make it easier for patients to search for suitable cancer apps.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 6 publications
0
30
1
1
Order By: Relevance
“…Of these, one paper was excluded as it was not relevant and a further five papers were removed as they were based on unpublished or unreleased apps (not available in online stores). This left 13 papers for inclusion in our final review [12][13][14][15][16][17][18][19][20][21][22][23][24] (Fig. 1).…”
Section: Study Selectionmentioning
confidence: 99%
See 4 more Smart Citations
“…Of these, one paper was excluded as it was not relevant and a further five papers were removed as they were based on unpublished or unreleased apps (not available in online stores). This left 13 papers for inclusion in our final review [12][13][14][15][16][17][18][19][20][21][22][23][24] (Fig. 1).…”
Section: Study Selectionmentioning
confidence: 99%
“…The app group had significantly less burden in emotional functioning, insomnia, and urinary-related symptoms at the end of treatment and 3 months later than the control group Authors found that the app (which they developed) had a role in facilitating supportive care needs during cancer treatment Performed using non-randomised control trial This highlights the importance of early detection and management of symptoms (especially in anxiety and depression which can cause sleep disturbances), which can be facilitated by the use of the app Böhme et al [13] Evaluation of the quality and accuracy of mobile cancer apps…”
Section: Studies Related To 'App Readability'mentioning
confidence: 99%
See 3 more Smart Citations